REHABILITATION OF MASTICATION AND LACK OF SPACE TREATMENT IN NARROW EDENTULOUS WITH FIXED-FIXED BRIDGE - Rahmad Arifin; Fitriana Caessar Pertiwi (FKG Unlam, 2021)
Background: Loss of posterior teeth can lead to disharmony in the curvature of the jaw. Antagonistic teeth and surrounding teeth will migrate to the edentulous causing reduced mastication function and TMJ disturbance. Several cases of narrow edentulous occurred due to tooth shifting caused by edentulous that was left empty for a long period. Creating a fixed-fixed bridge is aimed to restore the aesthetics, function, and comfort for patients which caused by the missing teeth. Fixed-fixed bridge consist of a retainer that function as a support to the abutment; a pontic that function to replace the missing tooth; and a connector that function to connect the pontic and the retainer. A narrow space for pontics can disrupt the aesthetic and functional aspects. Case Report: A 24 year-old male patient was referred to Prosthodontic Clinic, Gusti Hasan Aman Dental Hospital with a complain of pain on the jaw joint and missing of left lower molar for about 5 years. Patient always masticate on one side after the left lower molar was missing. Extraoral examination found the patient to be in good condition, no enlargement of major salivary glands, the vital signs were good, but upon TMJ examination there was clicking sounds on the left side. Intraoral examination showed space narrowing resulted from mesial and distal drifting of 37 and 35 but not significant, therefore it was still possible to perform rehabilitation using fixed-fixed bridge with abutments on 37 and 35 with modification of pontic shape for 36 to resemble a premolar tooth with occlusal surface resembling a molar tooth. Treatment planning for fixed prosthetic using fixed-fixed bridge with porcelain fused to metal material on 35, 36, and 37 with ridge lap pontic type modification Conclusions: Treatment was successful to provide enough space for the pontic by modification of the shape and the size of the pontic. Keywords: Fixed-fixed bridge. lack of space, mastication.